Ultra-low hydration heat cementing material and preparation method thereof

Ultra-low-hydrated thermal gelling materials prepared by using cement clinker of specific proportions and particle sizes, granulated blast furnace slag and fly ash and other raw materials in natural gas hydrate mining, solve the lack of applicability of the existing technology in low temperature environments. The problem of hydration temperature rise is achieved lower than the decomposition temperature of natural gas hydrate, reducing mining risks, and improving the strength and cost-effectiveness of the materials.

CN119191733APending Publication Date: 2024-12-27SOUTH CHINA UNIV OF TECH
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411236021.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-04
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing low-thermal gelling materials are insufficiently applicable in low-temperature environments, which cannot effectively reduce the risk of decomposition during natural gas hydrate mining. The hydration exothermic characterization method is limited, and the particle density and accumulation space structure are not considered.

Method used

Using ultra-low hydration thermal gelling materials, mixing cement clinker, granulated blast furnace slag and fly ash and other raw materials through specific proportions, combined with the close packing theory, the hydration temperature rise is lower than the decomposition temperature of natural gas hydrate at low temperatures. The cemented materials include cement clinker, fine, medium and coarse granulated blast furnace slag, graded fly ash and gypsum, and the water-gluing ratio is controlled between 0.45 and 0.50. The particle size and density of the particles are taken into account during the stirring and maintenance process. Ensure the structure is dense.

Benefits of technology

The hydration temperature rise at low temperature is lower than the decomposition temperature of natural gas hydrate, reducing the risk of mining, and the hydration and heat exotherm conditions are clear, the strength is moderate, the cost is low, and the process is simple. It is suitable for natural gas hydrate mining.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005027745160000071
    Figure BDA0005027745160000071
  • Figure BDA0005027745160000081
    Figure BDA0005027745160000081
Patent Text Reader

Abstract

The invention belongs to the technical field of cementitious material preparation, and particularly relates to an ultralow-hydration-heat cementitious material and a preparation method thereof. The ultralow-hydration-heat cementing material is prepared from the following raw materials in parts by weight: 1 to 5 parts of cement clinker, 12 to 46 parts of granulated blast-furnace slag in a fine-granularity interval, 16 to 20 parts of granulated blast-furnace slag in a medium-granularity interval, 18 to 51 parts of granulated blast-furnace slag in a coarse-granularity interval, 0 to 26 parts of graded fly ash and 15 parts of gypsum. According to the ultralow-hydration-heat cementing material provided by the invention, the main raw materials come from industrial waste residues, the energy consumption is low, the heat release is low, and the hydration temperature rise is lower than the decomposition temperature (less than 12 DEG C) of natural gas hydrate; on the basis of the close packing theory, particles with different particle sizes and raw materials with different proportions are reasonably used, the space structure is fully utilized, the structure is more compact, and therefore high strength is achieved. The cementing material has very important guiding significance on exploitation of natural gas hydrates.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of gelling material preparation, and in particular relates to an ultra-low hydration thermal gelling material and a preparation method thereof. Background Art

[0002] Economic and social development cannot be separated from the support of energy. In particular, natural gas, as a clean, high-quality, efficient and low-cost energy source, is increasingly in demand. Natural gas hydrate is a clathrate compound mainly formed by methane gas and water, commonly known as "combustible ice", which can be regarded as highly compressed natural gas.

[0003] Natural gas hydrates usually exist on the seabed at a temperature of 4 to 5°C. The temperature and pressure conditions for the stable existence of natural gas hydrates are -20 to 12°C and 200 to 600 Pa. If the threshold is exceeded, natural gas hydrates will face the risk of decomposition, which will have an adverse effect on their exploitation. Therefore, in order to alleviate the decomposition of natural gas hydrates during the exploitation process and improve the exploitation efficiency, an ultra-low hydration thermal gelling material is urgently needed in a low temperature environment (5°C).

[0004] In the prior art, the authorization announcement CN116282977 "A low-heat cementitious material and its preparation method" solves the contradiction between early strength and low hydration heat in the composition system of silicate cement-based cementitious materials in the prior art by mixing cement clinker, graded fly ash, gypsum, activator, and regulator in a certain proportion.

[0005] The above technical solution may cause the following problems during actual use:

[0006] (1) The experimental conditions set in this invention are room temperature, while natural gas hydrates usually exist on the low-temperature (4-5°C) seabed. Therefore, it lacks reference significance for this application scenario.

[0007] (2) The present invention directly characterizes the hydration heat release through the specific value of the hydration heat. However, natural gas hydrates exist in an appropriate temperature range, and the amount of hydration heat release cannot be directly measured by temperature, which has certain limitations for practical applications.

[0008] (3) The present invention mixes different graded granular raw materials without considering the density and specific numerical conditions of the particles, and lacks consideration of the spatial structure of particle stacking. Summary of the invention

[0009] In order to solve the above technical problems, the present invention proposes an ultra-low hydration thermal gelling material and a preparation method thereof for use in natural gas hydrate exploitation under low temperature conditions (4-5°C). The hydration temperature rise of the gelling material at low temperature is lower than the decomposition temperature of natural gas hydrates, and the strength at each age is moderate (the maximum 28d strength can reach 19MPa), thereby effectively reducing the risk of decomposition of natural gas hydrates during exploitation.

[0010] The present invention is achieved through the following technical solutions:

[0011] An ultra-low hydration thermal gelling material, comprising the following raw materials by weight:

[0012] 1-5 parts of cement clinker, 12-46 parts of granulated blast furnace slag in the fine particle size range, 16-20 parts of granulated blast furnace slag in the medium particle size range, 18-51 parts of granulated blast furnace slag in the coarse particle size range, 0-26 parts of graded fly ash, and 15 parts of gypsum;

[0013] Among them, the median particle size of granulated blast furnace slag in the fine particle size range is 2 to 5 μm, the median particle size of granulated blast furnace slag in the medium particle size range is 8 to 12 μm, and the median particle size of granulated blast furnace slag in the coarse particle size range is 20 to 30 μm.

[0014] Furthermore, the ultra-low hydration thermal gelling material includes the following raw materials by weight: 1 to 5 parts of cement clinker, 30 to 46 parts of granulated blast furnace slag in a fine particle size range, 16 to 19 parts of granulated blast furnace slag in a medium particle size range, 18 to 34 parts of granulated blast furnace slag in a coarse particle size range, 0 to 26 parts of graded fly ash, and 15 parts of gypsum.

[0015] Furthermore, the total weight proportion of the fine-grained blast furnace slag, the medium-grained blast furnace slag and the coarse-grained blast furnace slag (total amount of graded granulated blast furnace slag) is 80-84 parts.

[0016] Furthermore, the cement clinker is ordinary Portland cement clinker with a median particle size of 15 to 19 μm, and its composition includes C3S, C2S, C3A, and C4AF.

[0017] Further preferably, the median particle size of the cement clinker is 19 μm.

[0018] Furthermore, the median particle size of the granulated blast furnace slag in the fine-grained range is 3.05 μm, the 28d activity index at room temperature is 101-105%, and the 28d activity index at a low temperature of 5°C is 27-29%; the median particle size of the granulated blast furnace slag in the medium-grained range is 10.71 μm, the 28d activity index at room temperature is 74-79%, and the 28d activity index at a low temperature of 5°C is 12-15%; the median particle size of the granulated blast furnace slag in the coarse-grained range is 25.22 μm, the 28d activity index at room temperature is 41-43%, and the 28d activity index at a low temperature of 5°C is 7-11%.

[0019] Furthermore, the apparent density of the fine-grained interval granulated blast furnace slag is 3.00 g / cm 3 The apparent density of medium-sized granulated blast furnace slag is 3.01 g / cm 3 The apparent density of coarse-grained granulated blast furnace slag is 3.15 g / cm 3 .

[0020] Furthermore, the graded fly ash includes fine-grained fly ash and coarse-grained fly ash; the median particle size of the fine-grained fly ash is 5.94 μm, and the apparent density is 2.32 g / cm 3 The median particle size of fly ash in the coarse particle size range is 52.9 μm, and the apparent density is 2.03 g / cm 3 ;

[0021] Furthermore, the gypsum is natural dihydrate gypsum.

[0022] Furthermore, the raw materials of the ultra-low hydration thermal gelling material also include sand;

[0023] Further preferably, the sand is standard sand; the amount of the sand used is 250 to 350 parts by weight.

[0024] The method for preparing the ultra-low hydration thermal gelling material comprises the following steps:

[0025] (1) Cement clinker, fine-grained blast furnace slag, medium-grained blast furnace slag, coarse-grained blast furnace slag, graded fly ash, and gypsum are mixed in proportion and precooled in a low-temperature curing box at 4 to 5° C. for 2 to 3 hours;

[0026] (2) placing the pre-cooled mixture in a mixer and stirring it with an automatic control program, with a water-cement ratio of 0.45 to 0.50, stirring at a low speed for 30 to 40 seconds, then stirring at a low speed for 30 to 40 seconds while automatically adding sand, stirring at a high speed for 30 to 40 seconds, stopping for 90 to 100 seconds, and then stirring at a high speed for 60 to 70 seconds to obtain the corresponding cement mortar;

[0027] (3) The obtained cement mortar is injected into a mold and placed in a low-temperature incubator at 4 to 5°C for curing.

[0028] Furthermore, in step (3), the low speed is 120-160 r / min, and the high speed is 260-300 r / min;

[0029] Furthermore, the curing time in step (3) is 3 to 28 days.

[0030] Furthermore, the precooling temperature in step (1) is 5° C. and the time is 2 hours.

[0031] Furthermore, the curing temperature in step (3) is 5°C.

[0032] Compared with the prior art, the present invention has the following advantages:

[0033] (1) The hydration heat release of the cementitious material of the present invention is low, and the hydration temperature rise caused by the hydration heat release is lower than the decomposition temperature of natural gas hydrates, thus having a guiding role in the exploitation of natural gas hydrates.

[0034] (2) The present invention directly and clearly measures the hydration exothermicity of the hydration temperature rise reaction, and has strong quantitative properties. It can be directly compared with the decomposition temperature of natural gas hydrate, which is more practical.

[0035] (3) The present invention is based on the close packing theory and rationally utilizes particles of different particle sizes and raw materials of different proportions. The spatial structure is fully utilized, making the structure denser, thereby achieving higher strength.

[0036] (4) The cementitious material of the present invention does not need to be calcined, but the raw materials are ground to a certain fineness and mixed evenly. The production process is simple, and most of the components are mineral admixtures (granulated blast furnace slag), which can fully utilize industrial slag, is low in cost, and is an energy-saving cementitious material.

[0037] (5) The ultra-low hydration heat gelling material of the present invention has low hydration heat, and the hydration heat release is concentrated in the first two days.

[0038] <12℃, which is lower than the decomposition temperature of natural gas hydrate; the 3-day strength is ≥3MPa, the 7d strength is >7MPa, and the 28d strength is >8MPa, which has guiding significance for the exploitation of natural gas hydrate. DETAILED DESCRIPTION

[0039] The following examples further illustrate the technical solution of the present invention, but are not intended to limit the scope of protection of the present invention.

[0040] The parameters of the materials used in the following examples of the present invention are as follows:

[0041] The median particle size of granulated blast furnace slag (unclassified) is 13.15 μm, the activity index of 28 days at room temperature is 95-98%, the activity index of 28 days at low temperature (5°C) is 15-20%, and the apparent density is 2.86 g / cm 3 ;

[0042] The median particle size of the fine particle size range of granulated blast furnace slag is 3.05μm, the activity index of 28d at room temperature is 101-105%, the activity index of 28d at low temperature (5℃) is 27-29%, and the apparent density is 3.00g / cm 3 ;

[0043] The median particle size of the medium particle size range is 10.71 μm, the 28-day activity index at room temperature is 74-79%, the 28-day activity index at low temperature (5°C) is 12-15%, and the apparent density of the medium particle size range is 3.01 g / cm 3 ;

[0044] The median particle size of the coarse particle size range is 25.22 μm, the 28-day activity index at room temperature is 41-43%, the 28-day activity index at low temperature (5°C) is 7-11%, and the apparent density of the coarse particle size range is 3.15 g / cm 3 .

[0045] The median particle size of fly ash fine particle size range is 5.94 μm, and the apparent density is 2.32 g / cm 3 ; The median particle size of the coarse particle size range is 52.9 μm, and the apparent density is 2.03 g / cm 3 .

[0046] The cement clinker is ordinary Portland cement clinker with a median particle size of 19 μm, and its composition includes C3S, C2S, C3A, and C4AF.

[0047] The "parts" in the following examples of the present invention are based on weight.

[0048] Example 1

[0049] The raw materials used in this embodiment are as follows:

[0050] 5 parts of cement clinker, 46 parts of fine-grained blast furnace slag, 16 parts of medium-grained blast furnace slag, 18 parts of coarse-grained blast furnace slag, and 15 parts of gypsum.

[0051] (1) Cement clinker, graded granulated blast furnace slag and gypsum are mixed in the above proportions and precooled in a 5°C low temperature curing box for 2 hours;

[0052] (2) The pre-cooled mixture is placed in a mixer and stirred with an automatic control program, with a water-cement ratio of 0.45 (w / c), at a low speed (140±5 r / min) for 30 seconds, then at a low speed for another 30 seconds while automatically adding 300 portions of standard sand, at a high speed (285±10 r / min) for 30 seconds, then stopped for 90 seconds, and then at a high speed for 60 seconds to obtain the corresponding cement mortar;

[0053] (3) The obtained cement mortar was injected into a 40 mm × 40 mm × 160 mm mold and placed in a 5°C low-temperature incubator for curing.

[0054] The fluidity of cement mortar was measured according to GB / T 2419-2005 standard; the strength after curing for 3 days, 7 days and 28 days was tested according to GB / T 17671-1999 standard; the heat release of cement mortar was measured according to GB / T12959-2008 standard (direct method). The performance test results are shown in Table 1.

[0055] Example 2

[0056] 5 parts of cement clinker, 37 parts of fine-grained blast furnace slag, 16 parts of medium-grained blast furnace slag, 27 parts of coarse-grained blast furnace slag, and 15 parts of gypsum.

[0057] (1) Cement clinker, graded granulated blast furnace slag and gypsum are mixed in proportion and placed in a 5°C low temperature curing box for precooling for 2 hours;

[0058] (2) The pre-cooled mixture is placed in a mixer and stirred with an automatic control program, with a water-cement ratio of 0.45 (w / c), at a low speed (140±5 r / min) for 30 seconds, then at a low speed for another 30 seconds while automatically adding 300 portions of standard sand, at a high speed (285±10 r / min) for 30 seconds, then stopped for 90 seconds, and then at a high speed for 60 seconds to obtain the corresponding cement mortar;

[0059] (3) The obtained cement mortar was injected into a 40 mm × 40 mm × 160 mm mold and placed in a 5°C low-temperature incubator for curing.

[0060] The fluidity of cement mortar was measured according to GB / T 2419-2005; the strength after 3 days, 7 days and 28 days was tested according to GB / T 17671-1999; the heat release of cement mortar was measured according to GB / T12959-2008 (direct method). The performance test results are shown in Table 1.

[0061] Example 3

[0062] 5 parts of cement clinker, 30 parts of fine-grained blast furnace slag, 16 parts of medium-grained blast furnace slag, 34 parts of coarse-grained blast furnace slag, and 15 parts of gypsum.

[0063] (1) Cement clinker, graded granulated blast furnace slag and gypsum are mixed in proportion and placed in a 5°C low temperature curing box for precooling for 2 hours;

[0064] (2) The pre-cooled mixture is placed in a mixer and stirred with an automatic control program, with a water-cement ratio of 0.45 (w / c), at a low speed (140±5 r / min) for 30 seconds, then at a low speed for another 30 seconds while automatically adding 300 portions of standard sand, at a high speed (285±10 r / min) for 30 seconds, then stopped for 90 seconds, and then at a high speed for 60 seconds to obtain the corresponding cement mortar;

[0065] (3) The obtained cement mortar was injected into a 40 mm × 40 mm × 160 mm mold and placed in a 5°C low-temperature incubator for curing.

[0066] The fluidity of cement mortar was measured according to GB / T 2419-2005; the strength after 3 days, 7 days and 28 days was tested according to GB / T 17671-1999; the heat release of cement mortar was measured according to GB / T12959-2008 (direct method). The performance test results are shown in Table 1.

[0067] Example 4

[0068] 5 parts of cement clinker, 35 parts of granulated blast furnace slag in fine particle size range, 19 parts of granulated blast furnace slag in medium particle size range, 26 parts of fly ash in coarse particle size range, and 15 parts of gypsum.

[0069] (1) Cement clinker, graded granulated blast furnace slag, graded fly ash and gypsum are mixed in proportion and placed in a 5°C low temperature curing box for precooling for 2 hours;

[0070] (2) The pre-cooled mixture is placed in a mixer and stirred with an automatic control program, with a water-cement ratio of 0.45 (w / c), at a low speed (140±5 r / min) for 30 seconds, then at a low speed for another 30 seconds while automatically adding 300 portions of standard sand, at a high speed (285±10 r / min) for 30 seconds, then stopped for 90 seconds, and then at a high speed for 60 seconds to obtain the corresponding cement mortar;

[0071] (3) The obtained cement mortar was injected into a 40 mm × 40 mm × 160 mm mold and placed in a 5°C low-temperature incubator for curing.

[0072] The fluidity of cement mortar was measured according to GB / T 2419-2005; the strength after 3 days, 7 days and 28 days was tested according to GB / T 17671-1999; the heat release of cement mortar was measured according to GB / T12959-2008 (direct method). The performance test results are shown in Table 1.

[0073] Example 5

[0074] 5 parts of cement clinker, 16 parts of granulated blast furnace slag in fine particle size range, 16 parts of granulated blast furnace slag in medium particle size range, 35 parts of granulated blast furnace slag in coarse particle size range, 13 parts of fly ash in fine particle size range, and 15 parts of gypsum.

[0075] (1) Cement clinker, graded granulated blast furnace slag, graded fly ash and gypsum are mixed in proportion and placed in a 5°C low temperature curing box for precooling for 2 hours;

[0076] (2) The pre-cooled mixture is placed in a mixer and stirred with an automatic control program, with a water-cement ratio of 0.45 (w / c), at a low speed (140±5 r / min) for 30 seconds, then at a low speed for another 30 seconds while automatically adding 300 portions of standard sand, at a high speed (285±10 r / min) for 30 seconds, then stopped for 90 seconds, and then at a high speed for 60 seconds to obtain the corresponding cement mortar;

[0077] (3) The obtained cement mortar was injected into a 40 mm × 40 mm × 160 mm mold and placed in a 5°C low-temperature incubator for curing.

[0078] The fluidity of cement mortar was measured according to GB / T 2419-2005; the strength after 3 days, 7 days and 28 days was tested according to GB / T 17671-1999; the heat release of cement mortar was measured according to GB / T12959-2008 (direct method). The performance test results are shown in Table 1.

[0079] Example 6

[0080] 5 parts of cement clinker, 32 parts of granulated blast furnace slag in fine particle size range, 17 parts of granulated blast furnace slag in medium particle size range, 18 parts of granulated blast furnace slag in coarse particle size range, 13 parts of fly ash in coarse particle size range, and 15 parts of gypsum.

[0081] (1) Cement clinker, graded granulated blast furnace slag, graded fly ash and gypsum are mixed in proportion and placed in a 5°C low temperature curing box for precooling for 2 hours;

[0082] (2) The pre-cooled mixture is placed in a mixer and stirred with an automatic control program, with a water-cement ratio of 0.45 (w / c), at a low speed (140±5 r / min) for 30 seconds, then at a low speed for another 30 seconds while automatically adding 300 portions of standard sand, at a high speed (285±10 r / min) for 30 seconds, then stopped for 90 seconds, and then at a high speed for 60 seconds to obtain the corresponding cement mortar;

[0083] (3) The obtained cement mortar was injected into a 40 mm × 40 mm × 160 mm mold and placed in a 5°C low-temperature incubator for curing.

[0084] The fluidity of cement mortar was measured according to GB / T 2419-2005; the strength after 3 days, 7 days and 28 days was tested according to GB / T 17671-1999; the heat release of cement mortar was measured according to GB / T12959-2008 (direct method). The performance test results are shown in Table 1.

[0085] Comparative Example 1

[0086] 5 parts of cement clinker, 80 parts of granulated blast furnace slag (unclassified), and 15 parts of gypsum.

[0087] (1) Cement clinker, granulated blast furnace slag and gypsum are mixed in proportion and placed in a 5°C low temperature curing box for precooling for 2 hours;

[0088] (2) The pre-cooled mixture is placed in a mixer and stirred with an automatic control program, with a water-cement ratio of 0.45 (w / c), at a low speed (140±5 r / min) for 30 seconds, then at a low speed for another 30 seconds while automatically adding 300 portions of standard sand, at a high speed (285±10 r / min) for 30 seconds, then stopped for 90 seconds, and then at a high speed for 60 seconds to obtain the corresponding cement mortar;

[0089] (3) The obtained cement mortar was injected into a 40 mm × 40 mm × 160 mm mold and placed in a 5°C low-temperature incubator for curing.

[0090] The fluidity of cement mortar was measured according to GB / T 2419-2005; the strength after 3 days, 7 days and 28 days was tested according to GB / T 17671-1999; the heat release of cement mortar was measured according to GB / T12959-2008 (direct method). The performance test results are shown in Table 1.

[0091] Comparative Example 2

[0092] 1 part of cement clinker, 84 parts of granulated blast furnace slag (unclassified), and 15 parts of gypsum.

[0093] (1) Cement clinker, granulated blast furnace slag and gypsum are mixed in proportion and placed in a 5°C low temperature curing box for precooling for 2 hours;

[0094] (2) The pre-cooled mixture is placed in a mixer and stirred with an automatic control program, with a water-cement ratio of 0.45 (w / c), at a low speed (140±5 r / min) for 30 seconds, then at a low speed for another 30 seconds while automatically adding 300 portions of standard sand, at a high speed (285±10 r / min) for 30 seconds, then stopped for 90 seconds, and then at a high speed for 60 seconds to obtain the corresponding cement mortar;

[0095] (3) The obtained cement mortar was injected into a 40 mm × 40 mm × 160 mm mold and placed in a 5°C low-temperature incubator for curing.

[0096] The fluidity of cement mortar was measured according to GB / T 2419-2005; the strength after 3 days, 7 days and 28 days was tested according to GB / T 17671-1999; the heat release of cement mortar was measured according to GB / T12959-2008 (direct method). The performance test results are shown in Table 1.

[0097] Table 1 Properties of ultra-low hydration thermal gelling materials

[0098]

[0099]

Claims

1. An ultra-low hydration thermal gelling material, characterized in that: The following raw materials are included by weight: 1-5 parts of cement clinker, 12-46 parts of granulated blast furnace slag in the fine particle size range, 16-20 parts of granulated blast furnace slag in the medium particle size range, 18-51 parts of granulated blast furnace slag in the coarse particle size range, 0-26 parts of graded fly ash, and 15 parts of gypsum; Among them, the median particle size of granulated blast furnace slag in the fine particle size range is 2 to 5 μm, the median particle size of granulated blast furnace slag in the medium particle size range is 8 to 12 μm, and the median particle size of granulated blast furnace slag in the coarse particle size range is 20 to 30 μm.

2. The ultra-low hydration thermal gelling material according to claim 1, characterized in that: Calculated by weight, the raw materials include: 1-5 parts of cement clinker, 30-46 parts of granulated blast furnace slag in fine particle size range, 16-19 parts of granulated blast furnace slag in medium particle size range, 18-34 parts of granulated blast furnace slag in coarse particle size range, 0-26 parts of graded fly ash and 15 parts of gypsum.

3. The ultra-low hydration thermal gelling material according to claim 1, characterized in that: The total weight proportion of the fine-grained blast furnace slag, the medium-grained blast furnace slag and the coarse-grained blast furnace slag is 80-84 parts.

4. The ultra-low hydration thermal gelling material according to claim 1, characterized in that: The cement clinker is ordinary Portland cement clinker with a median particle size of 15 to 19 μm, and its composition includes C3S, C2S, C3A and C4AF.

5. The ultra-low hydration thermal gelling material according to claim 1, characterized in that: The median particle size of the granulated blast furnace slag in the fine particle size range is 3.05 μm, the 28d activity index at room temperature is 101-105%, and the 28d activity index at 5°C is 27-29%; the median particle size of the granulated blast furnace slag in the medium particle size range is 10.71 μm, the 28d activity index at room temperature is 74-79%, and the 28d activity index at 5°C is 12-15%; the median particle size of the granulated blast furnace slag in the coarse particle size range is 25.22 μm, the 28d activity index at room temperature is 41-43%, and the 28d activity index at 5°C is 7-11%.

6. The ultra-low hydration thermal gelling material according to claim 1, characterized in that: The apparent density of the fine-grained blast furnace slag is 3.00 g / cm 3 The apparent density of medium-sized granulated blast furnace slag is 3.01 g / cm 3 The apparent density of coarse-grained granulated blast furnace slag is 3.15 g / cm 3 .

7. The ultra-low hydration thermal gelling material according to claim 1, characterized in that: The graded fly ash includes fine-grained fly ash and coarse-grained fly ash; the median particle size of the fine-grained fly ash is 5.94 μm, and the apparent density is 2.32 g / cm 3 The median particle size of fly ash in the coarse particle size range is 52.9 μm, and the apparent density is 2.03 g / cm 3 ; The gypsum is natural dihydrate gypsum.

8. The ultra-low hydration thermal gelling material according to claim 1, characterized in that: The raw materials of the ultra-low hydration thermal gelling material also include sand; the sand is standard sand; and the amount of the sand is 250 to 350 parts by weight.

9. The method for preparing the ultra-low hydration thermal gelling material according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) Cement clinker, fine-grained blast furnace slag, medium-grained blast furnace slag, coarse-grained blast furnace slag, graded fly ash, and gypsum are mixed in proportion and precooled in a low-temperature curing box at 4 to 5° C. for 2 to 3 hours; (2) placing the pre-cooled mixture in a mixer and stirring it with an automatic control program, with a water-cement ratio of 0.45 to 0.50, stirring at a low speed for 30 to 40 seconds, then stirring at a low speed for 30 to 40 seconds while automatically adding sand, stirring at a high speed for 30 to 40 seconds, stopping for 90 to 100 seconds, and then stirring at a high speed for 60 to 70 seconds to obtain the corresponding cement mortar; (3) The obtained cement mortar is injected into a mold and placed in a low-temperature incubator at 4 to 5°C for curing.

10. The preparation method according to claim 9, characterized in that: In step (3), the low speed is 120-160 r / min, and the high speed is 260-300 r / min; The curing time in step (3) is 3 to 28 days.

Citation Information

Patent Citations

  • Preparation method of composite cement with low clinker dosage and high flexural compression ratio

    CN101948255A

  • All-solid-waste-based low-carbon green ecological cementing material and manufacturing method thereof

    CN115321848A

  • Low-heat cementing material and preparation method thereof

    CN116282977A

  • Spheroidized low-heat Portland slag cement and preparation method thereof

    CN117700127A

  • Environmental protection and energy-saving early-strength slag cement

    CN1721354A